Rheumatology symptoms and syndromes - Benenson, E. V. (Efim V.) (Springer, 2011)
Rheumatology: Symptoms and Syndromes organizes the rheumatic diseases in the form of syndromes as stable combinations of symptoms, and links these to morphological manifestations. This presentation of the rheumatic diseases provides a pedagogical framework for differential diagnosis in rheumatology. To further aid the teacher and student, Professor Efim Benenson provides algorithms of clinical reasoning based on morphology and pathophysiology. Professor Benensonâ??s practice-oriented, didactic approach, and innovative organization of the rheumatic diseases is a valuable diagnostic aid to practicing rheumatologists and those teaching or training in rheumatology. Readers are recommended the companion book, Rheumatology: Clinical Scenarios, for further reading on Professor Benensons's organization of the rheumatic diseases.